Determinants of Student Work Readiness: The Role of Internship Experience, Organizational Involvement, and Networking - Wijaya Agus Setiawan; Nurhadi (FEBI IAIN Langsa, 2026)
The increasing competitiveness of the modern labor market, driven by globalization and rapid technological change, has placed graduate work readiness as a pressing strategic concern in higher education. Despite extensive studies on internship and organizational experiences, limited research has examined the combined role of professional networking in shaping students' work readiness, particularly within the Indonesian higher education context. Grounded in Human Capital Theory and Social Capital Theory, this study analyzes the influence of Internship Experience, Organizational Involvement, and Networking on the work readiness of students at Universitas Pembangunan Nasional